Candidate genes associated with low temperature tolerance in cucumber adult plants identified by combining GWAS & QTL mapping - Caixia Li; Shaoyun Dong; Diane M. Beckles; Xiaoping Liu; Jiantao Guan; Zaizhan Wang; Xingfang Gu; Han Miao; Shengping Zhang (Stress Biology)
Abstract Fruit quality and yield are reduced when cucumber (Cucumis sativus L.) plants are exposed to low temperature (LT) stress, yet, the inheritance and genes linked to cold tolerance in adult plants have not been reported yet. Here, the LT-tolerance of 120 cucumber accessions representing four ecotypes were evaluated by GWAS, and also, in 140 recombinant inbred lines (RILs) derived from a biparental cross. Plants were exposed to naturally occurring LT environments in a plastic greenhouse, in winter 2022, and 2023, and a low temperature injury index (LTII) was employed to evaluate plant performance. Genetic analysis revealed that the LT-tolerance evaluated in the adult cucumber plants was a multigenic quantitative trait, and that 18 of the 120 accessions were highly LT tolerant by our LTII assessment. Two loci (gLTT1.1 and gLTT3.1) exhibited strong signals that were consistent and stable in two environments. In addition, two QTLs—qLTT1.2 on chromosome (Chr.) 1, and qLTT3.1 on Chr. 3, were discovered in all tests using RIL population derived from a cross between LT-sensitive ‘CsIVF0106’, and LT-tolerant ‘CsIVF0168’. qLTT1.2 was delimited to a 1.24-Mb region and qLTT3.1 was narrowed to a 1.43-Mb region. Interestingly, a peak single nucleotide polymorphism (SNP) at gLTT1.1 and gLTT3.1 was also found in qLTT1.2 and qLTT3.1, respectively. These loci were thus renamed as gLTT1.1 and gLTT3.1. In these regions, 25 genes were associated with the LT response. By identifying differences in haplotypes and transcript profiles among these genes, we identified four candidates: CsaV3_1G012520 (an ethylene-responsive transcription factor) and CsaV3_1G013060 (a RING/U-box superfamily protein) in gLTT1.1, and two RING-type E3 ubiquitin transferases at CsaV3_3G018440 and CsaV3_3G017700 in gLTT3.1 that may regulate LT-tolerance in adult cucumber. Interestingly, the accessions in which the LT-tolerant haplotypes for two loci were pyramided, displayed maximally high tolerance for LT. These findings therefore provide a solid foundation for the identification of LT-tolerant genes and the molecular breeding of cucumber with LT-tolerance.